Sistem Adaptasi dan Etika Lingkungan Masyarakat Adat Terhadap Kegiatan Pariwisata di Kampung Naga - Mardyalita Mandasari; Zailla Nurul Jannah; Raisya Rifatun Nabila; Muhammad Akram Al Farisy; Fauzi Alfauzan; Yani Sri Astuti (Universitas 45 Surabaya, 2024)
This research aims to understand the adaptation of the Kampung Naga community to changes resulting from tourism activities, while maintaining environmental and cultural sustainability, as well as its impact on the economic, social and cultural conditions of indigenous communities. Kampung Naga is very interesting to learn about so it attracts the interest of outsiders to visit. This causes changes in society as a form of adaptation to tourism activities. The research method used in this research is a qualitative descriptive method which describes a phenomenon, human behavior or conditions in a particular place in the form of narratives or images. The research results show that there are adaptations made by the community as a response to the changes that occur when traditional villages become tourist villages. The community shows a forward and open mindset as a form of adaptation to changes brought about by tourists. Changes in community activities as a form of adaptation and adjustment to tourism activities. Suitability and adaptation of community objects to the needs and comfort of visitors.